Your guide to good shelter : how to plan, build, or convert for energy conservation - Waschek, Carmen; Washeck, Brownlee (Reston, Virginia : Reston Publishing Company, Inc., 1978)
This book is a practical guide to help you plan and build your home, or convert certain elements to save money and energy. It contains sound, proven information, not idle theories. This volume deals not only with cost and energy conservation, but with the human aspects of building and living a home. It is not written as an architectural textbook filled with detailed technicalities over which your ultimately have no control. It is a realistic book, written in language you understand, and detailing with situations you will encounter. It is written from experience.
Preface -- Acknowledgments -- Introduction -- PART 1. PLANNING: 1. Vocabulary -- 2. Selecting and buying your lot -- 3. What's your lifestyle going to be? -- 4. Be innovative -- 5. Housekeeping and maintenance -- 6. Look at materials -- 7. Lighting -- 8. Energy conservation -- 9. New ideas in energy efficiency -- 10. Energy-efficient living -- 11. Security features -- 12. Build a healthy environment -- 13. Safety features -- 14. Placements of house on lot -- 15. Landscaping -- PART 2. GETTING DOWN TO BUSINESS: 16. Financing -- 17. Getting your plans -- 18. Selecting your builder -- 19. How to cut costs -- 20. Inflation-fighting specifics -- 21. Building contract -- PART 3. BUILDING PROCESS: 22. Step-by-step building -- 23. Relationships with workmen -- 24. Final inspection -- Postscript -- Appendix 1. Estimate your home-building power -- Appendix 2. Suppliers of home plans -- Index.
Includes index.
Keywords: HOUSE CONSTRUCTION